Holland's RIASEC Model: Career and Job Development Assessment for Personnel Administration Staff - Pramudawardani, Ni Komang Putri; Adiati, Rosatyani Puspita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Individual assessment research with the RIASEC model based on Holland was conducted on employees with the aim of mapping the competencies that must be developed by an employee and knowing employee interests. This research uses descriptive research methods through case studies and the sample in this study is an employee with the position of Personnel Administration Staff at PT.X company. This study conducted an assessment of two positions, namely the current position as Personnel and an alternative position, namely Compensation & Benefit Staff. In addition to conducting assessments on both positions and the RIASEC test to map the subject's interests, the author also categorizes the two positions based on the world of work map theory. The results of the individual assessment will provide an overview of the employee's potential and suitability with his/her career interests. The assessment results show that the subject is more recommended for the Personnel Administration Staff position because the subject's personality type tends to like routine, order and administrative work (conventional type).Penelitian asesmen individu dengan model RIASEC berdasarkan Holland dilakukan terhadap karyawan dengan tujuan untuk memetakan kompetensi yang harus dikembangkan oleh seorang karyawan serta mengetahui minat karyawan. Penelitian ini menggunakan metode penelitian deskriptif melalui studi kasus dan sampel dalam penelitian ini adalah seorang karyawan dengan jabatan Personnel Administration Staff pada perusahaan PT.X. Penelitian ini melakukan asesmen pada dua jabatan yaitu jabatan saat ini sebagai Personnel dan jabatan alternatif yaitu Staff Compensation & Benefit. Selain melakukan asesmen pada kedua jabatan dan tes RIASEC untuk memetakan minat subyek, penulis juga melakukan kategorisasi pada kedua jabatan berdasarkan teori world of work map. Hasil asesmen individu akan memberikan gambaran potensi karyawan dan kesesuaian dengan minat karier yang dimilikinya. Hasil asesmen menunjukkan subyek lebih direkomendasikan ke dalam posisi Personnel Administration Staff dikarenakan tipe kepribadian subyek cenderung menyukasi rutinitas, keteraturan dan pekerjaan yang administratif (tipe conventional).